2007
DOI: 10.1016/j.amjhyper.2007.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Inflammation and Fibrosis Are Related to Cardiovascular Damage in Hypertensive Patients with Metabolic Syndrome

Abstract: Cardiovascular damage is more frequent in hypertensives with MS than in hypertensives without MS, and this is significantly related to the increased levels of inflammation and fibrosis found in hypertensives with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 31 publications
1
61
1
5
Order By: Relevance
“…In agreement with these studies, we found a significant association between lower levels of TGF-β1 and TGF-β2 and an increased risk of recurrent VTE. In contrast, other studies have shown an association between TGF-β and the development of metabolic syndrome and cardiovascular damage [24,25]. TGF-β was also weakly associated with factor VII in patients with hypercholesterolemia [26].…”
Section: Discussioncontrasting
confidence: 39%
“…In agreement with these studies, we found a significant association between lower levels of TGF-β1 and TGF-β2 and an increased risk of recurrent VTE. In contrast, other studies have shown an association between TGF-β and the development of metabolic syndrome and cardiovascular damage [24,25]. TGF-β was also weakly associated with factor VII in patients with hypercholesterolemia [26].…”
Section: Discussioncontrasting
confidence: 39%
“…Although a wide range of serum TNF-a levels has been reported in different populations, our results suggests a TNF-a cut-point value that is consistent with the recently reported range of control subjects. TNF-a levels of normotensive subjects were significantly lower than levels found in hypertensive individuals with MS diagnosis (23). Moreover, TNF-a levels differed between hypertensive subjects with or without MS.…”
Section: Discussionmentioning
confidence: 60%
“…MetS is known to be associated with deterioration in LV systolic and diastolic functions [3][4][5]. Myocardial fibrosis is thought to be one of the contributors to this deterioration [6,7,18]. Myocardial fibrosis can be diagnosed histopathologically and with the help of cardiac magnetic resonance imaging and scintigraphic methods [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…MetS has been shown to be associated with left ventricular (LV) systolic and diastolic dysfunctions [3][4][5]. The mechanism behind cardiac impairment in MetS is multifactorial, but one of the pivotal contributors is thought to be myocardial fibrosis [6,7].…”
Section: Introductionmentioning
confidence: 99%